Learning in later life: a bicultural perspective from Aotearoa/New Zealand. Issue 5 (2nd September 2016) - Findsen, Brian
Abstract: This article is concerned with how learning in later life has been constructed and practised by the two most numerous ethnic groups in Aotearoa/New Zealand, Pākėhā (Europeans) and Māori (Indigenous people). It is argued that learning is heavily influenced by historic features of interaction between these two groups; Pākehā as the dominant cultural and economic group and Māori as subordinate. While contemporary perspectives are necessarily interpreted in the light of historical trends and events, fresh interpretations of what constitutes biculturalism in this country allow for more nuanced understanding of possibilities for and obstacles to older adult learning/education. Themes from lifelong learning are analysed with special reference to older people's learning, the consequences of Māori sovereignty on pedagogy and trends identified for older adult education. Two linked case studies of Pākehā and Māori older adult education in a New Zealand university are described to illustrate complexities and tensions in provision in a bicultural context.